Students' Perception of the Use of Video Conference Application (Zoom Cloud Meetings) in Fostering EFL Learners' Speaking Ability on Speech - Muhamad Muklas; Fitria Wardani; Jelita; Hardiansyah (Channing : Journal of English Language Education and Literature, 2023)
This thesis is entitled "Students' Perception on the Use of Video Conference Application (Zoom Cloud Meetings) in Fostering EFL Learners' Speaking Ability Speech".  The presented study aimed to find out students' perception of using a video conference application (Zoom Cloud Meetings) in the virtual speech class of Nurul Huda University Sukaraja Buay Madang Oku Timur. The method used in this study was the descriptive qualitative method. The results of this study were: that using Zoom Cloud Meetings as an online platform for conducting English speech classes was adequately effective, students also showed a positive response to using the Zoom Cloud Meetings application. So that online learning can run smoothly. There are only a few differences in activities that happened during the English speech virtual classroom and English speech conventional classroom, the problems that often occur during the class are poor internet connection and internet quota, and some solutions implemented make it better for the students to looking for a strategic place with the stable internet signal inside, sharing each notes of the material, and decided to use Wireless Fidelity (WiFi) in their houses.